Artificial intelligence as part of digitalization of electric transport and agricultural engineering in the Kazakhstan and international law in the future - Sarsembayev, M.A.; Karazhan, B.S. (Bulletin of the Karaganda University “Law Series”, 2023)
The purpose of the proposed study is to show the worldwide and domestic relevance of such a phenomenal fact as artificial intelligence at the present time. To a certain extent, it can replace a person by responding with human speech as an operator to questions asked to him, perform production actions at industrial, ma[1]chine-building plants, participate in the production of electric vehicles, unmanned vehicles and agricultural machinery, drive unmanned vehicles, tractors, combines. Artificial intelligence is already being introduced into the production processes of transport and agricultural machinery plants of the Republic of Kazakhstan. In the future, artificial intelligence technologies will be used to a large extent in all spheres of public life in Kazakhstan, including in all branches of mechanical engineering. The introduction of these technologies in our country will be facilitated by the legislative acts of the Republic of Kazakhstan proposed and analyzed by the authors. In addition, the same process will be facilitated by international and international legal documents (including those proposed by the authors) on the use and development of artificial intelligence. This scientific article reveals the advantages of artificial intelligence, shows its usefulness for people, countries, and the world community, and suggests ways to limit the mechanisms of artificial intelligence in case they get out of human control.